TAS49--a dispersed repetitive sequence isolated from subtelomeric regions of Nicotiana tomentosiformis chromosomes - Horáková, M; Fajkus, J (Genome, 2000)
We have isolated and characterized a new repetitive sequence, TAS49, from terminal restriction fragments of Nicotiana tomentosiformis genomic DNA by means of a modified vectorette approach. The TAS49 was found directly attached to telomeres of N. tabacum and one of its ancestors, N. tomentosiformis, and also at inner chromosome locations. No association with telomeres was detected neither in N. otophora nor in the second tobacco ancestor, N. sylvestris. PCR and Southern hybridization reveal similarities in the arrangement of TAS49 on the chromosomes of 9 species of the genus Nicotiana, implying its occurrence as a subunit of a conserved complex DNA repeat. TAS49 belongs to the family of dispersed repetitive sequences without features of transposons. The copy number of TAS49 varies widely in the genomes of 8 species analyzed being lowest in N. sylvestris, with 3300 copies per diploid genome. In N. tomentosiformis, TAS49 forms about 0.56% of the diploid genome, corresponding to 17400 copies. TAS49 units are about 460 bp long and show about 90% of mutual homology, but no significant homology to DNA sequences deposited in GenBank and EMBL. Although genomic clones of TAS49 contain an open reading frame encoding a proline-rich protein similar to plant extensins, no mRNA transcript was detected. TAS49 is extensively methylated at CpG and CpNpG sites and its chromatin forms nucleosomes phased with a 170 +/- 8 bp periodicity.
Keywords: jedovaté rostliny; Molecular Sequence Data; Sequence Analysis, DNA; Genes, Plant; Sequence Homology, Nucleic Acid; Southernův blotting; nukleozomy; repetitivní sekvence nukleových kyselin; polymerázová řetězová reakce; Polymerase Chain Reaction; rostlinné geny; Blotting, Southern; Nucleosomes; Chromatin; Cloning, Molecular; Base Sequence; sekvence nukleotidů; restrikční mapování; tabák; Plants, Toxic; Plasmids; sekvenční analýza DNA; klonování DNA; Restriction Mapping; Telomere; telomery; plazmidy; sekvenční homologie nukleových kyselin; chromatin; molekulární sekvence - údaje; Nicotiana; Repetitive Sequences, Nucleic Acid